Artificial intelligence all-in-one - Minnick, Chris; Allan, Jeffrey; Baker, Pamela, 1957-; Diamond, Stephanie; Lindsell-Roberts, Sheryl; Massaron, Luca; Mladjenovic, Paul; Mueller, John, 1958-; Singh, Shiv; Stanton, Daniel (--For dummies., 2025)
"Artificial intelligence is everywhere. Major software organizations like Microsoft, Google, and Apple have built AI directly into products and invited the world to become part of the AI revolution. And it's impossible to use these tools to their fullest potential without understanding the basics of what AI is and what it can do"--